The Connections of the Contents of Anuthinrerairaiwan: the Creativity in the Essays of the Preschool Children - Wiwan, Boonlert; Janphen , Sairak; Klinbanyong, Aphanut (JOURNAL OF RATTANA PAÑÑĀ, 2020)
The research article, the connections of the contents of Anuthinrerairaiwan: the creativity in the essays of the preschool children, found that there were seven connection strategies: references that usually used pronouns such as “them” and “us”; representations that usually used “this” and “both” as well as those occasionally used for representing pronouns, verbs and sentences; omissions that mostly were word omissions; complete repetitions that usually used nouns such as “mother”, “father” and “brother/sister” as well as partial repetitions that used words for calling relatives such as “grandfather-grandpa” and “grandmother-grandma”; conjunctions consisting of five sub-strategies (i.e. similarities, oppositions, alternatives, rationales and times); vocabularies including three types of vocabularies (i.e. similar, opposite and same types of vocabularies); and content connections that were used in single statements. It was found that three to seven strategies were used as follows: partial repetitions, complete repetitions, representations, references, conjunctions, omissions and vocabularies.